Migration and Development - Macha Farrant; Anna MacDonald; Dhananjayan Sriskandarajah (United Nations, 2006)
There is growing consensus that international migration can have important impacts on development, and that it is important to develop appropriate and effective policy interventions that will help realize the full potential of international migration. This will require devising measures to harness the developmental potential that emigration from developing countries can bring while, at the same time, ensuring that the depletion of highly skilled workers does not damage development outcomes in the countries of origin. This paper is intended to guide policymakers through some of these challenges.